Factors Related to Weight Gain in DMPA (Depo Medroxy Progesterone Acetate) Acceptors - Adisti Rosadi, Della; Dinengsih, Sri; Suciati, Anni (Jurnal MIDPRO, 2023)
In Indonesia, injectable contraceptives are contraceptives that are in demand, about 34.3% of which are used by women of childbearing age. One of the shortcomings of DMPA hormonal injectable contraceptives is weight gain due to the presence of hormones that facilitate the change of carbohydrates and sugar into fat and stimulate the appetite control center in the hypothalamus which causes acceptors to eat more than usual. This study is to analyze the factors associated with weight gain in DMPA acceptors at TPMB "R" cijeruk Bogor West Java 2023. The research design used with Cross Sectional. The population in this study were DMPA user mothers at           TPMB "R" Cijeruk Bogor West Java Year 2023. The sampling technique used Purposive Sampling. The sample amounted to 129 people. Univariate and Bivariate data analysis That the age factor, length of use, physical activity, and eating habits with a p value <0.05, while the diabetes history factor with a p value> 0.05. There  is a significant relationship between the factors of age, length of use, physical activity, and eating habits with weight gain in DMPA acceptors, and there is no relationship between history of diabetes with weight gain. For acceptors can maintain and control body weight by exercising.